Creative Tourism as a promoter of the Sustainable Development Goals - Central Alentejo - Duarte, Eunice (2022)
This article aims to analyse creative tourism as a promoter of sustainable development goals (SDGs). To achieve the objective of the study, the questionnaire was applied to entrepreneurs who develop activities associated with creative tourism in Central Alentejo. For the literature review, the Science Direct, Emerald, and Google Scholar databases were used to investigate the correlation between creative tourism and SDG, namely through articles published between 2017-2020. The questionnaire survey was based on literature review. It was found that the state of the art focuses little on the relationship between creative tourism and the SDGs. Despite the focus on job creation, preservation of the environment, and culture, there seems to be a lack of attention to gender equity, social inclusion, and resource management. This study may have implications at the social level, allowing the understanding of the contribution of creative tourism to the cultural and environmental preservation of places, but also the need for more studies and strategies at the level of gender equality and social inclusion. The value of this article is related to the scarcity of studies in the area, as it allows us to have greater insight into the mindset of these entrepreneurs regarding this subject, as well as the relevance they attribute to each SDG